Investigation of The Effectiveness of Teucrium Orientale L. Plant in Hemorrhoid Treatment - Emin, Nuray; Nural, Kıymet; Güzel, Ayşegül (Turkish Science and Technology Publishing (TURSTEP), 2018)
Hemorrhoids are swollen vascular vein pads in the upper part of the anal canal. The deformations in these tissues cause serious disturbances, and most important one is hemorrhoid, which is a symptomatic degenerative disease. Due to various etiologic factors, weakening and disintegration of connective tissue cause this disease. Many methods have been developed in the treatment of hemorrhoids from the past to the present day, and drug therapy is used as primary care. However, surgical treatment methods are applied in advanced stages in which the disease can not be treated with medication and when there is a life-threatening risk. As alternative medicine applications, herbal remedies have been used in hemorrhoid treatment for centuries. Prepared herbal mixtures or extracts are still frequently preferred by the patients today. In this context, in the research we have carried out in Beyköy village of Havza district; Teucrium orientale L. are used by regional people in the treatment of hemorrhoids and it was detected that the awareness of this herbal treatment is limited. In this study, the efficacy of T. orientale L. plant in hemorrhoid treatment was evaluated by conducting a questionnaire survey on the patients using plant extract. Of the approximately 500 patients using plant extracts, 89 agreed to fill out the questionnaire. Due to the results of the survey, it was found that all of the patients using the extract of T. orientale L. plant are healed partly or completely, and the benefit from the extract changed according to the patient's age and the stage of the disease. There has been no study on the use of this plant in the treatment of hemorrhoids in literature, and it is the first study to be done in this respect.
Keywords: Teucrium Orientale L., haemorrhoids, plant extract, Beyköy, herbal remedies; S; Agriculture (General); Agriculture; S1-972; 3. Good health